CHARACTERISTIC OF LITORAL SEDIMENT ON SINDULANG SATU COASTAL - Korwa, Junet I. S.; Opa, Esry T.; Djamaludin, Rignolda (JURNAL PESISIR DAN LAUT TROPIS, 2013)
Coastal area is defined as the interface point where sea and land meet. To the land the area is limited to the area influenced by the sea factors (wind, tide, and sea water infiltration), while to the sea is limited to the area influenced by the land factors. Special concern need to be addressed in regarding to the use of coastal area. As part of the coastal area, littoral zone is very dynamics due to factors of oceanography and human activities. The same fact is experienced by the littoral zone in Sindulang Satu. Physical change has been the fact in this littoral zone. Â In relation to the change, it is considered of importance to describe and analysis the characteristics of the sediment and related oceanography factors.Â  Result of observation indicated that sediment in the littoral zone consist of fine sand, medium sand, very fine sand, coarse sand and pebbles. Silt and boulder were also found. Distribution of sediment granulometry showed that the littoral zone was dominated by fine sand material, bad sorted, asymetrical to small size and symmetrical granulometry, and mesokurtic. Tidal current is the type of current working in the littoral zone and it plays importance role in the sediment.